Narrativas infantis : experiências iniciais sobre a “escola de gente grande” - Pinheiro, Kelen Aparecida Galvão (2021)
This dissertation is the result of a master's research, originating from the Graduate Program in Education at the Federal University of Mato Grosso. Its study objective is the Children's Narratives as a path rich in knowledge and investigative possibilities to better understand the moment of transition from early childhood education to elementary school. The objective was to understand how the first experiences of children take place in the process of transition from early childhood education to school life in the first year of elementary school. The locus for conducting the research was a municipal school of basic education in the city of Sinop, in the interior of Mato Grosso, where the research participants consisted of a group of children aged 06 and 07 years old. The procedures for composing the field texts were: records written in the field notebook that compose the daily scenes between the children and their conversations. We also used the narrative interview with the children at different times, in addition to official documents from the school and the municipality, which served as the basis for understanding the municipal educational policy around this very important moment in school life. A qualitative approach and narrative research were adopted as a method and phenomenon based on the writings and concepts of Clandinin and Connelly, as they allow for a deepening in the understanding of concepts and relating them to daily life. Dewey was also sought to understand the most significant concept for the experiences. We return to historical paths, for theoretical basis in Kuhlmann Jr., Kishimoto, Kramer, in addition to the entire documentary framework accessed on the websites of the Federal Government, as historical documents that help us to understand the trajectory of the struggle of young Brazilian children. With regard to the school paths experienced by children during school life, Bernardin, Moss, Staccioli, among others, allow us to walk and realize the weaknesses and potentials between the moments of passages, as well as the importance of the play that permeates these passages, about this This question sustains us by authors such as Moyles, Winnicott, Lee, Vigotsky, seeking to make an approximation between the stages. The composition of the meanings constructed with the participants was organized into thematic axes that reveal the meanings given by the children to the new experience of being in elementary school. With the research, it was noticed that the vast majority of children really like to be in new spaces, with new colleagues and these novelties make them feel growing, feel bigger, and especially are inserted in a society that is immersed in a literate world. Reading and writing are synonymous with “being big” for them, however, they feel immense desire to do it in the most pleasurable way possible that would be playing as they did in kindergarten. It was also very evident that they would like to participate more actively and clearly in the welcoming process, saying what they would like to play with, where, how they would like to perform the tasks, where they would like to sit and eat, all these senses of being in a place and belonging to it at the same time, with which they did not identify in the reception.